Answer:
b- 4.4 * 10^-12.
Explanation:
Hello.
In this case, as the reaction:
A + 2B → 3C
Has an equilibrium expression of:
[tex]K_1=\frac{[C]^3}{[A][B]^2}=2.1x10^{-6}[/tex]
If we analyze the reaction:
2A + 4B → 6C
Which is twice the initial one, the equilibrium expression is:
[tex]K_2=\frac{[C]^6}{[A]^2[B]^4}[/tex]
It means that the equilibrium constant of the second reaction is equal to the equilibrium constant of the first reaction powered to second power:
[tex]K_2=K_1^2[/tex]
Thus, the equilibrium constant of the second reaction turns out:
[tex]K_2=(2.1 * 10^{-6})^2\\\\K_2=4.4x10^{-12}[/tex]
Therefore, the answer is b- 4.4 * 10^-12.
Best regards.